Investigation of heat transfer and hydraulic resistance in small-scale pillow-plate heat exchangers. (15th August 2019) - Arsenyeva, Olga; Piper, Mark; Zibart, Alexander; Olenberg, Alexander; Kenig, Eugeny Y.
Abstract: Pillow-Plate Heat Exchangers (PPHEs) represent an innovative equipment type, with space-effective, light and pressure-resistant construction. In this work, an experimental study of air cooling by water in small-scale PPHEs was carried out and an analysis of the hydraulic resistance and heat transfer was performed based on the experimental data. A semi-empirical correlation for friction factor inside pillow-plate panels which is based on main geometric parameters is proposed. This correlation is reliable in a wide range of Reynolds numbers, both for laminar and turbulent flow regime. For the external channel between pillow-plate panels, the correlations for pressure drop and heat transfer were obtained based on experimental data. The CFD simulations were carried out to investigate heat transfer in the external channel of the PPHE. The deviation between the experimental and simulated values of heat transfer coefficient is maximum 17%. The received correlations enable to calculate the overall heat transfer and pressure drop in small-scale PPHEs and can be applied for preliminary design of PPHEs. The case study of the PPHE application for water heating is considered. The designed heat exchanger with minimal heat transfer area has 30% less surface area then chevron-type plate heat exchangers traditionally used for such application. Highlights: The experimental set-up with small pillow-plate heat exchanger (PPHEs) is developed. The correlation for friction factor in inner channel of the PPHE is proposed. Friction factor and heat transfer coefficient in external PPHE channel are observed. The analysis of small-scale PPHE application for water heating is provided. The comparison of PPHEs with chevron-type plate heat exchangers is given.